1) ОДЗ:
Ответ : 3
2)
Проверка :
Верно
Ответ:
1) 3 2) 6
Объяснение:
1) 7 - x = x2 - 2x + 1
6 + x - x2 = 0
-x2 + x + 6 = 0
x2 - x - 6 = 0
D = 25
x1 = 1+5 | 2 = 3
x2 = 1-5 |2 = -2
Подставить и проверить
Ответ: x = 3
2) √x + 3 = 7-√3x-2
x+3=49-14√3x-2 + 3x-2
14√3x-2 = 47+3x-x-3
14√3x-2 = 44 +2x
7√3x-2 = 22+x
103x - 582 - x2 =0
x2 - 103x +582 = 0
D = 8281
x1 = 103 + 91 | 2=97
x2 = 103-91 |2 = 6
Ответ: x=6
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
1) ОДЗ:
Ответ : 3
2)
Проверка :
Верно
Verified answer
Ответ:
1) 3 2) 6
Объяснение:
1) 7 - x = x2 - 2x + 1
6 + x - x2 = 0
-x2 + x + 6 = 0
x2 - x - 6 = 0
D = 25
x1 = 1+5 | 2 = 3
x2 = 1-5 |2 = -2
Подставить и проверить
Ответ: x = 3
2) √x + 3 = 7-√3x-2
x+3=49-14√3x-2 + 3x-2
14√3x-2 = 47+3x-x-3
14√3x-2 = 44 +2x
7√3x-2 = 22+x
103x - 582 - x2 =0
x2 - 103x +582 = 0
D = 8281
x1 = 103 + 91 | 2=97
x2 = 103-91 |2 = 6
Подставить и проверить
Ответ: x=6